Saccharomyces and non-Saccharomyces Competition during Microvinification under Different Sugar and Nitrogen Conditions - Lleixà, Jessica; Manzano, Maria; Mas, Albert; Portillo, María del C. (Frontiers in Microbiology, 2016)
The inoculation of wines with autochthonous yeast allows obtaining complex wines with a peculiar microbial footprint characteristic from a wine region. Mixed inoculation of non-Saccharomyces yeasts and S. cerevisiae is of interest for the wine industry for technological and sensory reasons. However, the interactions between these yeasts are not well understood, especially those regarding the availability of nutrients. The aim of the present study was to analyze the effect of nitrogen and sugar concentration on the evolution of mixed yeast populations on controlled laboratory-scale fermentations monitored by density, plate culturing, PCR-DGGE and sugar and nitrogen consumption. Furthermore, the effect of the time of inoculation of Saccharomyces cerevisiae respect the initial co-inoculation of three non-Saccharomyces yeasts was evaluated over the evolution of fermentation. Our results have shown that S. cerevisiae inoculation during the first 48h conferred a stabilizing effect over the fermentations with non-Saccharomyces strains tested and, generally, reduced yeast diversity at the end of the fermentation. On the other hand, nitrogen limitation increased the time of fermentation and also the proportion of non-Saccharomyces yeasts at mid and final fermentation. High sugar concentration resulted in different proportions of the inoculated yeast depending on the time of S. cerevisiae inoculation. This work emphasizes the importance of the concentration of nutrients on the evolution of mixed fermentations and points to the optimal conditions for a stable fermentation in which the inoculated yeasts survived until the end.